Coastal Community Perception of Mangroves in Suli Subdistrict, Luwu - Sulaiman, B.; Bambang, A. N.; Purnaweni, H.; Lutfi, M.; Mohammed, E. M. A. (Jurnal Pendidikan IPA Indonesia, 2019)
Mangrove forest in the coastal area in the Suli subdistrict is one of the sources of livelihood for the local people. The objective of this research is to analyze the public perception of the coastal community towards mangrove forests. The analysis was carried out using a questionnaire-multilevel scale with the level of assessment that refers to the Likert scale. The questionnaires, which were disseminated to 100 respondents, contained questions about the public perception in the coastal mangrove area. The questions were divided into 5 part questions, namely: 4 questions for the public perception towards ecological functions, 7 questions for community participation, 5 questions for economic benefit, 5 questions for social and culture, and 5 questions for government regulation. The results revealed that the average of public perception towards the ecological functions of mangrove was good, with a value of 4.11 (in category 4). The public perception towards public participation was also good, with a value of 3.69 (in category 4). Moreover, the public perception about the economic benefits of mangrove was quite good, with a value of 3.37 (in category 3). The social and culture was quite good, with a value of 3.32 (in category 3). Finally, the public perception towards government regulation (law enforcement) was good, with a value of 3.57 (in category 4). Based on the results, the average value was 3.61, which means that mangroves management is good (in category 4) based on the perceptions of a coastal community in the Suli Subdistrict. The level of education does not affect the perception of the importance of mangrove management. This was caused by the existence of local wisdom, which considers that mangroves are the nails of the earth that can prevent coastal abrasion. This local wisdom is maintained up to now, where the local community formed a group of mangrove lovers that aims to plant and conserve mangroves.